Strengthening the Quality of Service Oriented to Medical Tourists: A Strategy for The Sustainability of The Hotel Sector in Barraquilla (2021)
Medical tourism has shown a sustained increase in recent years in Colombia. As part of the DNA in the dynamics of the hotel sector, the quality of service is a fundamental aspect that determines how the medical tourist perceives his stay. Therefore, quality of service is the variable that directs this research, measured through five factors: Tangible Elements, Reliability, Responsiveness, Security and Empathy. In this sense, an objective was established to determine the strengthening of the quality of service oriented to the medical tourist as a strategy for the sustainability of the hotel sector in Barranquilla. Based on a survey of 215 subjects, the results showed that the quality of service received by the medical tourist is poor. Concluding that this behavior corresponds to the business model that owns the hotel sector in Barranquilla (oriented to the attention of business tourists) where no improvements have been made to give a differentiating value proposal aimed at providing attention towards the medical tourist, as a strategy for its sustainability in the market. Keywords: Quality Of Service, Hospitality, Medical Tourism, Business